Vitamin D Mitigates Depression-related Disorders in an Animal Model of Depression: A Behavioral, Anatomopahtological, and Molecular Investigation, Implicating the Hippocampal BDNF Signaling Pathway - Filali, Houda; Kadil, Youness; Rahmoune, Imane; Adouani, Badr; Badr, Latifa; Agoub, Mohamed (Central Nervous System Agents in Medicinal Chemistry, 2025)
BackgroundMajor depressive disorder represents a complicated mental disorder characterized by persistent feelings of unhappiness and loss of interest. More evidence suggests a high potential correlation between vitamin D deficiency and depression. However, the underlying mechanisms and the therapeutic potential of vitamin D supplementation are still not properly understood. The purpose of this research is to evaluate the effect of vitamin D supplementation on depressive behaviors using a rat model of depression and explore the potential mechanisms involved.Depression is a prevalent mental health disorder that significantly impacts the quality of life of individuals. Despite the availability of various treatment options, many patients still experience suboptimal outcomes, highlighting the need for further exploration of novel therapeutic approaches. In recent years, the importance of vitamin D in mental health, particularly in depression, has gained considerable attention.MethodsIn this project, we propose to utilize an animal model of depressed rats to evaluate the effect of vitamin D supplementation on depressive behaviors. We employed a range of well-established behavioral tests to assess changes in depressive-like behaviors following vitamin D supplementation.Additionally, histopathological examinations of the hippocampal region, known to be involved in mood regulation, were performed to assess structural alterations and cellular changes associated with depression and vitamin D supplementation.ResultsThe findings demonstrate the therapeutic potential of vitamin D supplementation by improving neuronal reorganization and proliferation in the hippocampus, suggesting an interest in investigating other mechanisms of interaction.ConclusionThe findings of this research will provide valuable insight into the therapeutic potential of vitamin D in depression and shed light on the underlying mechanisms involved.
Keywords: rat model